2017
DOI: 10.1016/j.pharep.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Berberine attenuates cognitive impairment and ameliorates tau hyperphosphorylation by limiting the self-perpetuating pathogenic cycle between NF-κB signaling, oxidative stress and neuroinflammation

Abstract: BBR attenuated cognitive deficits and limited hyperphosphorylation of tau via inhibiting the activation of NF-κB signaling pathway, and by retarding oxidative stress and neuro-inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…Furthermore, intracerebral administration of STZ led to features characteristic of AD, including cognitive impairment and ACh homeostasis disturbances [160], which could be alleviated by insulin sensitizers [15,161]. Our literature survey indicated that berberine directly protects the brain cells against damages associated with dementia [27,29,32,34,39], possibly via antioxidative and anti-inflammatory effects [28,35,37,42], and also by reducing A levels [31,38]. Berberine was able to promote cognitive functions [38,40], through enhancing cholinergic neurotransmission [30,33,36,41].…”
Section: Direct Evidence Supporting Berberine's Antidementia Effectsmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, intracerebral administration of STZ led to features characteristic of AD, including cognitive impairment and ACh homeostasis disturbances [160], which could be alleviated by insulin sensitizers [15,161]. Our literature survey indicated that berberine directly protects the brain cells against damages associated with dementia [27,29,32,34,39], possibly via antioxidative and anti-inflammatory effects [28,35,37,42], and also by reducing A levels [31,38]. Berberine was able to promote cognitive functions [38,40], through enhancing cholinergic neurotransmission [30,33,36,41].…”
Section: Direct Evidence Supporting Berberine's Antidementia Effectsmentioning
confidence: 94%
“…Potential benefits were demonstrated in 16 nondiabetic studies (Table 1) and in 9 studies using diabetic models (Table 2). In nondiabetic models, berberine protected learning and memory in heavy metal-induced AD [28], Aβ-induced memory deficits model [34], familial AD models [29,35,38] and D-galactose-induced brain damage [40,145]. In the rat VaD model induced by chronic cerebral hypoperfusion, berberine protected hippocampal calyculin A1 (CA1) neurons and prevented memory deficit [27].…”
Section: Ischemia-reperfusion Injury In T2dmmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8] Moreover, a growing preclinical literature suggests that BBR has a broad number of antinfective activities, [9][10][11] and it could also exert some protective effects against neurodegenerative processes. 12 Also, recent data have shown that BBR could also exert some gastroprotective effects. 13 BBR has poor water solubility and its oral bioavailability is less than 5% and bowel P-glycoprotein contributes to this, actively expelling the alkaloid from the lumen mucosal cells.…”
mentioning
confidence: 99%